Treatment of Pesticides in Wastewater by Heterogeneous and Homogeneous Photocatalysis - Catalina Daniela Stan; Igor Cretescu; Cristina Pastravanu; Ioannis Poulios; Maria Drăgan (International Journal of Photoenergy)
The effect of different heterogeneous and homogeneous photocatalytic systems on the oxidative degradation of mepiquat chloride in aqueous solutions was investigated. In the case of heterogeneous reactions, the influence of five factors was studied: the type of catalyst, photocatalyst concentration, pH, pesticide concentration, and the presence of H2O2 and/or Fe3+. For homogeneous catalysis, other factors were studied: the oxidising agent and the light source. Nearly complete degradation of mepiquat chloride was obtained after about 180 minutes in the presence of an acid medium (pH3) using a UV-A lamp and TiO2P-25 catalyst (0.5 g/L), for an initial pesticide concentration of 10 ppm. Degradation rates corresponding to homogeneous photocatalysis were lower compared to those corresponding to the use of TiO2 as the photocatalyst.